Hirschsprung’s disease in adulthood: a case report - Leal, Clara; Fernandes, Urânia; Marques, Rita; Pinto-de-Sousa, João (International Surgery Journal, 2024)
Hirschsprung’s disease (HD) is caused by a gut development anomaly that leads to functional constipation. In most cases, HD is diagnosed and treated during childhood. Abdominal pain, distension and chronic constipation are typical symptoms of adult presentation. An adult HD case is presented, using analysis of electronic medical records and literature review for diagnostic and management insights. A man in his early 40s, with a history of chronic constipation since infancy, presented to the emergency department with an intestinal obstruction. Imaging tests revealed pronounced colonic dilation along with faecal loading. Following favourable progress, the patient was referred for outpatient investigation. Endoscopy revealed rectal scars with biopsy consistent with HD. A laparoscopic Duhamel-Martin procedure was performed in two stages. The postoperative period was uneventful. Adult HD is overlooked and misdiagnosed. Therefore, a high level of suspicion is needed to diagnose and avoid urgent surgeries, often with the need of colostomy and its particularities. When feasible, appropriate management by elective surgery should be the gold standard.